The Choice of Private Versus Public Capital Markets: Evidence from Privatizations - MEGGINSON, WILLIAM L.; NASH, ROBERT C.; NETTER, JEFFRY M.; POULSEN, ANNETTE B. (Journal of Finance, 2004)
ABSTRACT We examine the impact of political, institutional, and economic factors on the choice between selling a state‐owned enterprise in the public capital market through a share issue privatization (SIP) and selling it in the private capital market in an asset sale. SIPs are more likely in less developed capital markets, for more profitable state‐owned enterprises, and where there are more protections of minority shareholders. Asset sales are more likely when there is less state control of the economy and when the firm is smaller. Our results suggest the importance of privatization activities in developing the equity markets of privatizing countries.